A study on the interaction between local governments and tea in 19th century China from the perspective of capital theory: Centered on thе Hubei and Hunan region - Yao, Wei; Li, Yuhong (Faculty of Social and Political Science, Universitas Airlangga, 2024)
This study adopts a case study method to investigate the interaction between tea and the local government. From the 18th century to the early 20th century, black tea was an important export commodity of China’s Hubei and Hunan region (两湖地区). The black tea trade between the UK and the Hubei and Hunan region (两湖地区) had driven the rise of black tea cultural capital in the region. The cultural capital of black tea brought economic capital, and the local government increased fiscal revenue by levying likin on tea. The economic capital of black tea transformed into political capital, and the local government could compete with the central government and directly negotiate with foreign governments. To dump products onto China, the British government had to maintain the unity of the Chinese market, choose to ally with the central government and weaken the autonomy of the local government of the Hubei and Hunan region (两湖地区). The local governments turned to seeking support from Russia and developed the brick tea trade. This result led to the gradual inability of the national power represented by the central government to control local governments.